Development of screen-printed nickel-zinc and silver-zinc batteries - Muhamad Aiman Nazri (Kulliyyah of Engineering, International islamic University Malaysia, 2020)
The current trend for electronics demands portable, miniature, connected, and highly integrated devices, for example, wearable electronics and the internet of things (IoT). Miniaturization of these devices includes shrinking power sources or batteries. Compared to conventional batteries, printed batteries have relatively small form factors and are very thin. The printed battery is a battery system in which most of its components are printable. The batteries' elements, such as electrodes and ionic solutions, are developed in ink form such that it can be printed. For this work, a printed zinc battery was designed, fabricated using a screen printing method, and packaged in a pouch. The zinc battery system is chosen over lithium-ion batteries because of the abundance of zinc; zinc batteries are also cheaper, safe, and environmentally friendly. Screen printing was the fabrication method of choice as it is a widely used method, simple, and relatively cost-effective for research and development. In this research, two different battery systems were developed, compare both performances, which are Ni-Zn and Ag-Zn. Each of the battery elements (current collector, electrodes, electrolytes) were tested separately to evaluate its functionality and performance using electrochemical analyses such as cyclic voltammetry and charge-discharge. Through the experimental studies, polyvinyl butyral was selected as the binder of the battery electrodes due to its better electrochemical performance as compared to polyvinyl pyrrolidone, which is one of the crucial breakthroughs in this project. The selection of silver ink as the current collector was preferred since carbon ink has high resistance, which fails the battery. However, the silver ink is not suitable for cathode current collector, especially for the Ni-Zn system because it reacts on behalf of Ni(OH)2 due to its high reduction potential. Thus, the battery will function as an Ag-Zn battery instead, although the XRD data showed the presence of both Ni(OH)2 and ZnO on cathode and anode, respectively. The printed zinc-silver battery system was tested and was proven to work with a nominal voltage of 1.56V and a discharge capacity of 1.3407 mAh. The electrode surface area was found to be 8.78 cm2, which is equivalent to the areal capacity of 0.153 mAh.cm-2 with an overall thickness of 200-250 µm. This work is a proof-of-concept that zinc-silver batteries can be fabricated using screen printing techniques.